(3OjhGf GdCOHs - (3ESMGb Hf EHQGgje Hf GdMSjf GdaGQGHqj, CHh EHQGgje, J (B350 (3g` s
(3ChdgG (B:s
(3Chdg eHJhQ , hChd GdehLhO efg bhdg (B: (3J , GdHMJ (B: (3GdUQa , jbGd TQGH HMJ Ci hjbGd aQS HMJ Ci eMV , hGdHMK GdMSO s
(3BNQgG (B:s
(3BNQg eHJhQ , hBNQ GdehLhL efg HYfhGf (B"(3heeG LGA eVehe GdCda ecShQ GdMQa GdPi Ydi BNQg (B" (3bhdg (B: (3d , jbGd eGdi bO Yedg hcPG ai GdQLGd s
(3cJHJ YfhGfGJgG HGdMeQIs
(3eQJH Ydi GdChRGf hJOQL GdMQha GdCHLOjI ai BNQ GdhRfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B293s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GddZIs